P467 Therapeutic drug monitoring of biologics in Inflammatory Bowel Disease: Nordic survey on implementation and barriers in clinical practice. (21st January 2022) - Bjørlykke, K; Jahnsen, J; Brynskov, J; Molander, P; Eberhardson, M; Davidsdottir, L G; Sipponen, T; Hjortswang, H; Langholz, E; Jørgensen, K K; Steenholdt, C
Abstract: Background: Therapeutic drug monitoring (TDM) is a useful tool to optimise biologic treatments of patients with inflammatory bowel disease (IBD). Albeit broadly recommended by gastrointestinal societies, it is, however, currently unknown how TDM has been adopted and is being used in everyday clinical practice. The aim of the study was to investigate how TDM has been taken up by physicians including barriers for implementation. Methods: A web-based survey on TDM was distributed to all gastroenterology consultants in the Nordic countries via national gastroenterology- and IBD societies. Results: Out of 377 physicians responding, 297 handled IBD patients on biologic therapies and were thus eligible for inclusion (NO 118 (40%), DK 86 (29%), SE 50 (17%), FI 33 (11%), IS 10 (3%)). The vast majority were consultant gastroenterologists (n=252, 85%), 152 (51%) were employed at university hospitals, 136 (46%) at community hospitals, and 9 (3%) in private practice. Overall, 257 (87%) used TDM during biologic therapies; 231 (90%) used reactive TDM and 163 (63%) proactive TDM. Common indications were to improve efficacy (70%), aid treatment decisions (62%), improve safety (36%), and improve cost-effectiveness (32%). Notably, Danish physicians used TDM to a significantly lesser extent than all others (58% vs 98%; odds ratio (OR) 0.03 [95%CI 0.01- 0.09], p<0.001); in particular outside the capital region (OR 0.15 [0.05–0.46], p=0.001). Reactive TDM was applied both at primary (74%) and secondary treatment failure (99%) and predominantly for TNF-inhibitors (90–98%) (vedolizumab 63%, ustekinumab 46%). Proactive TDM was used by 80% during maintenance therapy and 56% during induction, and mostly for TNF-inhibitors (79–97%) (vedolizumab 70%, ustekinumab 54%). Proactive TDM was more commonly used in NO, SE, and FI (p<0.001), and by physicians managing >10 IBD patients per week (OR 2.71 [1.34–5.48], p=0.005), but was not associated with employment at university hospital, size of hospital catchment area, or seniority. Main barriers to the use of TDM were lack of guidelines (51%), long response time from the laboratory (49%), lack of knowledge regarding how to use and interpret test results (42%), costs (38%), and currently available evidence (31%). Among physicians using TDM, only 66% reported awareness of TDM guidelines or recommendations. Conclusion: TDM, and in particular reactive TDM of TNF-inhibitors, has been broadly adopted into clinical practice in the Nordic countries to improve efficacy and assist treatment decisions. Across the Nordic countries, IBD physicians call for improved test response times and, notably, TDM guidelines detailing indications for TDM and interpretation of test results.